Pre-treatment fertility counseling and fertility preservation improve quality of life in reproductive age women with cancer - Letourneau, Joseph M (2011)
BACKGROUND: The post-treatment quality of life (QOL) impacts of receiving pre-cancer-treatment infertility counseling and of pursuing fertility preservation have not been described in large-scale studies of reproductive age women with cancer. METHODS: 1041 women diagnosed between the ages of 18 and 40 responded to a retrospective survey and reported whether they received infertility counseling before cancer treatment and whether they took action to preserve fertility. Five cancer types were included: leukemia, Hodgkin’s disease, non-Hodgkin lymphoma, breast cancer, and gastrointestinal cancer. Validated QOL scales were used: Decision Regret Score (DRS), Satisfaction with Life Scale (SWLS), and World Health Organization QOL BREF (WHOQOL-BREF). RESULTS: 560 women (61%) whose treatment could affect fertility were counseled by the oncology team, 45 (5%) were counseled by fertility specialists, 36 (4%) took action to preserve fertility. Pre-treatment infertility counseling by a fertility specialist and an oncologist resulted in lower regret than counseling by an oncologist alone (8.4 vs. 11.0, P<0.0001). The addition of fertility preservation (6.6 vs. 11.0, P<0.0001) was also associated with even lower regret scores than counseling by an oncologist alone.. Further improvements were similarly seen in SWLS with the addition of fertility specialist counseling (23.0 vs. 19.8, P=0.09) or preserving fertility (24.0 vs. 19.0, P=0.05). CONCLUSIONS: Receiving specialized counseling about reproductive loss and pursuing fertility preservation is associated with less regret and greater QOL for survivors, yet few patients are exposed to this potential benefit. Reproductive aged women should have expert counseling and be given the opportunity to make active decisions about preserving fertility.